PENINGKATAN KEMAMPUAN KONSENTRASI MELALUI PERMAINAN BOWLING PADA ANAK AUTIS - KUSUMA WARDANA, DEVIT (Jurnal Pendidikan Khusus, 2017)
ABSTRACT In whatever activity it was surely required good concentration ability in order that the activity done would obtain maximum result. Autism children generally experienced disturbance in concentration especially focusing attention.With the disturbance in concentration ability the children’s activities in learning would be disturbed. This research purpose was to enhance the concentration ability to autism children through bowling game in SDLB PGRI Singojuruh Banyuwangi. This research was experiment with Single Subject Research (SSR) with A-B design. The subject of this research was autism children in SDLB PGRI Singojuruh who experienced concentration disturbance.Based on the analysis done it indicated that baseline phase (A) was done 4 sessions and intervention phase (B) was done 8 sessions meeting.According to the data analysis and discussion it could be concluded that there was enhancement of concentration ability to autism children after giving bowling game activity. Keywords: Bowling game, Concentration